Literary Criticism of Cross-Class Marriage in the Novel Heart of the Night Dialectical Perspective of George Wilhelm Friedrich Hegel - Tjalau, Cutri; R. Saleh, Sriwahyuningsih (Assuthur: Jurnal Pendidikan Bahasa Arab, 2024)
This study aims to analyze cross-class marriage in the novel "Heart of the Night" by Naguib Mahfouz using Hegel's dialectical perspective.  The research method used is a qualitative analysis of the content of the novel and the application of Hegel's dialectical theory to understand the conflict and synthesis in the marriage relationship between the main characters, Jafar Sayyed Ar-rawi, and Marwana.The purpose of this research is to explore the complexity of interclass marriage in the novel and identify the social, cultural, and economic conflicts that arise as a result of this relationship. In addition, this study aims to understand how Hegel's dialectical perspective can help in interpreting the dynamics of cross-class marriage in the context of a broader society. The results of the study show that the novel "Heart of the Night" depicts cross-class marriage as a reflection of social imbalances and disparities in society. The conflict between tradition and modernity, as well as economic and social inequalities, became obstacles to the marriage relationship of the main characters. However, Jafar Sayyed Ar-rawi showed perseverance and enthusiasm in maintaining his belief in bringing social justice to his people. Using Hegel's dialectical perspective, this study finds that the conflicts that arise from this cross-class marriage are forms of thesis and antithesis that contradict each other. However, through this struggle and conflict resolution, a synthesis was created that included understanding and unity between these figures. This synthesis reflects the importance of respecting social and cultural differences in a marriage as well as the possibility of searching for deeper meaning in life in the midst of a life full of challenges. This research illustrates that the novel "Heart of the Night" not only focuses on interclass marriage, but also highlights fortitude and enthusiasm in facing life's difficulties as well as the importance of conflict resolution and social understanding in society. With Hegel's dialectical approach, this study provides in-depth insights into the dynamics of social relations and marriage in the context of class differences in society.